Pengaruh Family Ownership, Foreign Ownership, dan Related Party Transaction Terhadap Real Earnings Management Dengan Gender Sebagai Variabel Moderasi - Alifia Maharani Gunarto; Vinola Herawaty (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The purpose of this study is to examine the effect of family ownership, foreign ownership, and related party transactions on real earnings management, with board gender diversity as a moderating variable. The population of this research consists of non-cyclical consumer companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. The data used in this study is quantitative. The sampling technique applied is purposive sampling, resulting in a sample of 79 companies. The analytical method employed in this research is linear regression analysis. The results of the analysis indicate that family ownership, foreign ownership, and board gender diversity do not significantly influence real earnings management. However, related party transactions are shown to have a positive effect on real earnings management. Furthermore, board gender diversity weakens the positive effect of related party transactions on real earnings management. This study has implications for understanding the factors influencing real earnings management practices within a company.